Influence of Financial Knowledge and Attitude on Financial Behavior of Working Women: Financial Self-Efficacy as a Mediator - Kunwar, Kripa; G. C., Surya Bahadur (Journal of Innovation in Academia, 2025)
Grounded on the Theory of Planned Behavior (TPB) and the Self-efficacy Theory, this study examines the influence of financial knowledge (FK), financial attitude (FA), and financial self-efficacy (FSE) on the financial behavior (FB) of working women through the mediating role of FSE in this relationship. Using the purposive sampling technique, data were collected from 309 working women working in different sectors. Data were analyzed using Smart PLS 4.0v. The findings revealed that FK did not support FB, whereas the FA and FB relationship was supported. Similarly, the relationship between FSE and FB was supported as well, and the mediating role of FSE was established in the relationship between FA and FB. FA and FSE emerged as significant predictors of FB of women, indicating the importance of psychological and motivational factors in shaping financial decisions. Policymakers and financial institutions should design targeted interventions that combine knowledge dissemination with confidence-building strategies.